Kompetensi Dan Independensi Auditor Dalam Pendeteksian Kecurangan Laporan Keuangan Pada Lima KAP Tertentu Di Jakarta - Marsella Runturambi; Jhon Rinendy; Meidy Karundeng (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Examining the impact of auditor independence and competence on the identification of fake financial statements at five designated KAPs in Jakarta is the primary objective of this research. The auditors employed by five separate Jakarta-based public accounting firms (KAP) are the subjects of this quantitative study. The questionnaire used a Likert scale as its measurement method, and 44 people participated in the sample. where the R2 coefficient, F test, and T test were measured as part of the multiple linear regression study. Findings from the study demonstrate that auditor independence and auditor competency significantly improve the likelihood of detecting financial statement fraud.